Pengaruh Budaya Organisasi, Pelatihan Dan Kompensasi Terhadap Kinerja Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Aceh Tamiang - Tama, Reno Putra; Sjafruddin, Sjafruddin (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
This study aims to determine and analyse the influence of organisational culture, training and compensation on the performance of the employees. This research aims to determine the effect of the independent variable X on the dependent variable Y and how strong the influence or relationship is. The research population consisted of all Investment and One-Stop Service Office employees of Aceh Tamiang Regency, totalling 39 people. Partially, organisational culture has no significant effect on performance. Partially, training does not have a significant effect on performance. Partially, compensation has a significant effect on performance. Simultaneously, organisational culture, training and compensation significantly influence the performance of the Aceh Tamiang District Investment and One-Stop Services Office employees. From the coefficient of determination, an R-value of 0.477 or 47.7% is obtained, which means that the relationship between performance and the independent variables, organisational culture, training and compensation is small. The R-Square value in this research is 0.227, which means 22.7% of the variation in performance is explained by the independent variables, namely organizational culture, training and compensation. While the remaining 77.3% is explained by other variables not examined in this study.